2009
DOI: 10.1104/pp.109.139220
|View full text |Cite
|
Sign up to set email alerts
|

BT2, a BTB Protein, Mediates Multiple Responses to Nutrients, Stresses, and Hormones in Arabidopsis      

Abstract: The Arabidopsis (Arabidopsis thaliana) gene BT2 encodes a 41-kD protein that possesses an amino-terminal BTB domain, a central TAZ domain, and a carboxyl-terminal calmodulin-binding domain. We previously demonstrated that BT2 could activate telomerase expression in mature Arabidopsis leaves. Here, we report its distinct role in mediating diverse hormone, stress, and metabolic responses. We serendipitously discovered that steady-state expression of BT2 mRNA was regulated diurnally and controlled by the circadia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
85
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 128 publications
(98 citation statements)
references
References 48 publications
1
85
0
Order By: Relevance
“…and BTB-TAZ4 genes, which were previously shown to be induced by nitrate but repressed by sugars (Mandadi et al, 2009). The inhibition of the TOR kinase results in the induction of autophagy (Wullschleger et al, 2006).…”
Section: Bric-a`-brac Tramtrack and Broad-transcriptional Adaptor Zimentioning
confidence: 93%
“…and BTB-TAZ4 genes, which were previously shown to be induced by nitrate but repressed by sugars (Mandadi et al, 2009). The inhibition of the TOR kinase results in the induction of autophagy (Wullschleger et al, 2006).…”
Section: Bric-a`-brac Tramtrack and Broad-transcriptional Adaptor Zimentioning
confidence: 93%
“…At-BT1 and 2 localize to the nucleus and cytosol, whereas At-BT3, 4, and 5 are cytosolic (Robert et al, 2009). At-BT proteins participate in Arabidopsis development, metabolic processes, and hormone signaling (Ren et al, 2007;Mandadi et al, 2009;Robert et al, 2009), and a role in abiotic stress has been suggested as they exhibit differential expression upon exposure to salt (At-BT2, 3, and 4) and cold stress (At-BT2, 3, and 5) (Du and Poovaiah, 2004;Mandadi et al, 2009). Furthermore, At-BT1, 2, and 5 are induced in plants overexpressing the salt toleranceconferring TF At-bZIP60, suggesting involvement of these At-BT proteins in protecting plants from salt stress (Fujita et al, 2007).…”
Section: Saltmentioning
confidence: 99%
“…For all qRT-PCR analysis, three independent biological replicates consisting of three plant samples each were used for total RNA isolation using Trizol reagent (Ambion), following the manufacturer's instructions. Two micrograms of the total RNA was used to make cDNA using SuperScript III first-strand cDNA synthesis kit (Invitrogen), as described previously (Mandadi et al, 2009), with minor modifications. Gene amplification by PCR was performed using Power SYBR Green Master-mix and the ABI Prism 7500 sequence detection system (Applied Biosystems).…”
Section: Rna Isolation Microarray and Qrt-pcr Analysismentioning
confidence: 99%